Nonlinear heave-roll coupling motions of cylindrical structures in sea wave - Tan, Desmond Jun Ming. (2009)
This project aims to study nonlinear vibration behaviours of floating systems through mathematically modelling and the application of numerical simulation. This report consists of two parts: first part is called mathematically modelling of floating cylinder and the second part is called dynamics study of cylinder – pendulum system. The first part included mathematical formulation of a floating cylinder in wave based on Newton’s second law, and a simple experiment in order to find out the damping coefficient, then by using Matlab’s ODE45 routine to integrate coupled equations, various plots were generated which include Phase portrait plot and Time Series plot, and through the observation of these plots, the basic characteristics of nonlinear dynamics can be studied. The second part included a further study of nonlinear dynamics based on cylinder – pendulum system, that a pendulum added inside the cylinder acted as a external force to reduce instability of the system. By varying some of the parameters, such as mass of the pendulum, the characteristics of nonlinear dynamic were recorded.